Constitutive Expression of hrap Gene in Transgenic Tobacco Plant Enhances Resistance Against Virulent Bacterial Pathogens by Induction of a Hypersensitive Response - Ger, M.J.; Chen, C-H.; Hwang, S-Y; Huang, H.; Podile, A.R.; Dayakar, B.V.; Feng, T.
Hypersensitive response-assisting protein (HRAP)has been previously reported as an amphipathic plant protein isolated from sweet pepper that intensifies the harpinPss-mediated hypersensitive response (HR). The hrap gene has no appreciable similarity to any other known sequences, and its activity can be rapidly induced by incompatible pathogen infection. To assess the function of the hrap gene in plant disease resistance, the CaMV 35S promoter was used to express sweet pepper hrap in transgenic tobacco. Compared with wild-type tobacco, transgenic tobacco plants exhibit more sensitivity to harpinPss and show resistance to virulent pathogens (Pseudomonas syringae pv. tabaci and Erwinia carotovora subsp. carotovora). This disease resistance of transgenic tobacco does not originate from a constitutive HR, because endogenous level of salicylic acid and hsr203J mRNA showed similarities in transgenic and wildtype tobacco under noninfected conditions. However, following a virulent pathogen infection in hrap transgenic tobacco, hsr203J was rapidly induced and a micro-HR necrosis was visualized by trypan blue staining in the infiltration area. Consequently, we suggest that the disease resistance of transgenic plants may result from the induction of a HR by a virulent pathogen infection.